Modernism, space and the city : outsiders and affect in Paris, Vienna, Berlin, and London - Thacker, Andrew, 1962- (Edinburgh critical studies in modernist culture., 2019)
This innovative text examines the development of modernist writing in four European cities: London, Paris, Berlin and Vienna.